Lixiviation as a tool for radionuclide fractionation in holm oak leaves (JOURNAL OF RADIOANALYTICAL AND NUCLEAR CHEMISTRY-ARTICLES, 1996)
A sequential extraction scheme, using distilled water and chloroform : hexane(1:2) was applied in a study of radionuclide retention by helm oak leaves. To perform this study, holm oak leaves were contaminated by dry deposition using a thermogenerated radioactive aerosol containing Cs-134, Sr-85 and Ag-110m. The experimental parameters tested were: type and lime of shaking, number of successive extractions in each step, and the volume of extractans. From the results obtained, two schemes which give complementary information about radionuclide retention are proposed. The first scheme, using a single water extraction with mechanical shaking, allows us to define two fractions: the fraction removed by water, which is related to total radionuclide retention on leaf surfaces, and the residual fraction, which is associated with radionuclides incorporated into the leaves. The second scheme is based on a two-step extraction with manual shaking using water and chloroform :hexane, and permits us to distinguish among three fractions:the fraction removed by water(which is related to the radionuclide fraction easily leached by rain), the fraction removed by organic solvent (which is associated with the radionuclide fraction strongly retained on leaf surface), and the residual fraction, which may represent the absorbed radionuclide content. Since our objective was to study the retention of Cs-134, Sr-85 and Ag-110m, simultaneously, the experimental conditions chosen were a compromise of individual suitable conditions for each radionuclide.
APS